2007
DOI: 10.1902/jop.2007.060458
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Concentrations of Interleukin‐23 and ‐17 at Healthy Sites and at Sites of Clinical Attachment Loss

Abstract: Our results suggested the possibility that the IL-23/IL-17 immune response was present within chronically inflamed gingiva. This is a host response that had not been reported previously in periodontal disease and may be an important factor in the chronic nature of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 48 publications
8
72
2
2
Order By: Relevance
“…4 In relation to chronic periodontitis, a significant elevation of the total amount of IL-17 had been demonstrated in the gingival crevicular fluid samples and culture supernatants of gingival cells in periodontitis patients compared to healthy controls that suggested a role for IL-17 in the pathogenesis of chronic periodontitis. 5 The involvement of IL-17 in the host response of periodontal disease is further supported by Lester et al 6 , who reported an increased concentration of IL-17 in gingival tissue supernatants at sites with moderate to severe CAL and had found a positive correlation between them at the site-based level.…”
Section: Introductionmentioning
confidence: 84%
“…4 In relation to chronic periodontitis, a significant elevation of the total amount of IL-17 had been demonstrated in the gingival crevicular fluid samples and culture supernatants of gingival cells in periodontitis patients compared to healthy controls that suggested a role for IL-17 in the pathogenesis of chronic periodontitis. 5 The involvement of IL-17 in the host response of periodontal disease is further supported by Lester et al 6 , who reported an increased concentration of IL-17 in gingival tissue supernatants at sites with moderate to severe CAL and had found a positive correlation between them at the site-based level.…”
Section: Introductionmentioning
confidence: 84%
“…Importantly, increased P. gingivalis-induced expression of heterodimeric IL-23, composed of p40 and p19, and connected to Th17 survival, were consistent with pro-inflammatory IL-17 ϩ cells within the lesions and inflamed gingiva. 58 IL-17 in turn accelerates innate cell recruitment and activation through IL-8, CXCL1, TNF, GM-CSF, and facilitates osteoclastogenesis. 59 One of the hallmarks and most devastating aspects of periodontal disease is the destruction to the supporting structures of the tooth, involving osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are thus consistent with the elevated levels of IL-17 in human periodontitis [4,[93][94][95] and in mouse periodontitis models [74,96]. IL-17 was also shown to stimulate antimicrobial immunity and thereby to inhibit pathogen-initiated bone loss in a relatively acute periodontitis model [97];…”
Section: Resultssupporting
confidence: 88%
“…To our knowledge, the abrogation of periodontitis in Oel-r / --IL-17R- [4,[93][94][95] and in mouse periodontitis models [74,96]. IL-17…”
Section: Discussionmentioning
confidence: 99%